Influence of postactivation potentiation on shot put performance of collegiate throwers - Judge, L. W.; Bellar, D. M.; Craig, B. W.; Gilreath, E. L.; Cappos, S. A.; Thrasher, A. B. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this investigation was to determine the acute effects of heavy and light implements on subsequent overhead back (OHB) shot put performance with a competition weight shot put. This investigation was designed to test the efficacy of heavy implements for potentiating subsequent OHB performance. Participants included 41 athletes (20.9 ± 1.18 years.) from 2 National Collegiate Athletic Association Division I schools in the Midwestern United States (n = 23 male and n = 18 female). Mean distance for OHB throw with a competition shot put was examined after treatment (control, light shot put warm-up, and heavy shot put warm-up) through repeated-measures analysis of variance (ANOVA) with post hoc Bonferroni-corrected post hoc analysis. Responses after treatment on the 10-cm visual analog scale (VAS) fatigue were examined through repeated-measures ANOVA and demonstrated a significant main effect for treatment on VAS fatigue (F = 16.463; p = 0.001). The heavy shot put warm-up resulted in the greatest mean performance over the course of the 3 attempts (14.39 ± 1.82 m) followed by the light shot put warm-up (14.18 ± 1.68 m) and the control (14.15 ± 1.70 m). Results of the repeated-measures ANOVA demonstrated a significant main effect for treatment in regard to average distance (F = 6.276; p = 0.003). Post hoc testing suggested that the heavy shot put warm-up resulted in significantly better mean OHB performance than either the light shot put warm-up (t = 2.983; p = 0.0048; ES = 0.472; power = 0.901) or the control shot put warm-up (t = 3.349; p = 0.0018; effect size [ES] = 0.513; power = 0.939). Subsequent analysis examined the relationship between reported fatigue accrued during the overweight shot put warm-up and the change in performance on the OHB throw when compared to the control condition. Analysis revealed that subjects who reported higher levels of VAS fatigue did not perform as well after the overweight treatment (p = 0.0274).